Character Education Management of Three Religion-Based Private High Schools In East Kalimantan - Sjamsir, Hasbi; Devung, Simon; Masruhim, H. Muh. Amir; Ritha, Aniah; Arya Sunu, I Gusti Ketut (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2023)
This study aims to describe the concept of character education management and the results management of character education in private religious-based private high schools. This study uses a qualitative approach with descriptive research type. Data collection techniques are carried out through interviews, observation and documentation. Data were analyzed using Miles and Huberman’s interactive model including data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that character education includes systematic-integrative based planning, implementation using habituation, modeling behavior, integration of extracurricular, intracurricular and co-curricular programs, formation of a conducive environment, as well as supervision through internal control in the form of rules and attitude books, while externally through visits House. The results of character education management in religious-based private high schools are knowing and experiencing multiculturalism which has implications for students’ attitudes of tolerance.